Pemanfaatan Kain Perca Untuk Meningkatkan Keterampilan Remaja Di Desa Tulang Bawang Baru - Dwi Rahmawati; Mentari Puspadini; Nur Ikhwanudin (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Efforts in utilizing patchwork are held training in making brooches. This training was given to teenagers aged 11-15 years in Tulang Bawang Baru village RT 03 RW 01, totaling 15 teenagers. The method used in presenting data is quantitative method. Data collection techniques were carried out using interview and observation techniques. This training aims to determine the improvement of youth skills. The assessment is seen from the aspect of neatness of patchwork, the harmony of colors and materials combined, and the accuracy of techniques in making brooches. The value of the product is seen from the aspect of neatness, including neatness of folds, neatness of stitches, neatness of patchwork arrangement, and neatness of glue and thread residue. In this aspect, 12 teenagers received very good scores. The value of the product seen from the aspect of harmony includes: harmony of patchwork, harmony of mote size, harmony of color, and harmony of the amount of material. In this aspect, there were 9 teenagers who scored very good. The value of the product seen from the aspect of accuracy includes: accuracy in placing the safety pin, accuracy of the technique in making the brooch, accuracy of the size of the brooch, and accuracy of the shape of the mote used. In this aspect, 12 teenagers scored very well. From the results of the study, it is known that the score achieved is 92% and is included in the excellent category. It means that the teenagers' skills improved very well.